Os Impactos da Convenção-Quadro para o Controle do Tabaco na Região Sudeste do Paraná: o caso CEDEJOR - Alves, Lúzia Aparecida (Teoria e Prática em Administração, 2014)
We aimed to analyze the actions performed in a region of growing tobacco due to the Framework Convention on Tobacco Control, a guideline that aims to reduce the production and consumption of this product The region is the southeastern Paraná has sustained its economy in the Integrated production whose central company Souza Cruz. Was used as a case study the Center for Development of Rural Youth (Cedejor), an intervention funded by Souza Cruz Institute aimed at training young farmers through the Pedagogy of Alternation. The techniques of data collection were semi-structured interviews, observation and document analysis, data were analyzed using content analysis and reconstitution of the facts allowed us to understand every aspect examined guided by movement of totality. The real movement is contradictory: the Convention requires reducing the supply and consumption of tobacco; the actions increased the planting area, the quantity produced and the number of families involved in the integrated production system (IPS), but that in the medium term, will be excluded from the system by increasing the quality of the commodities produced.